Nitrogênio em períodos do estabelecimento de capim Mombaça - Rodrigues, Márcio Odilon Dias (Universidade Federal do Tocantins, 2017)
Proper nitrogen levels for forage establishment period is crucial to maintaining sward, with vigorous and productive tillers in subsequent cycles, in this sense, the nitrogen fertilization is critical as it contributes directly to the synthesis of tissues and maintaining productivity. Given the above, the objective was to evaluate the effect of nitrogen in mombaça (Panicum maximum Jacq.) during the period of establishment. The experiment conducted in Araguaína, TO, for 45° days, starting on the 15° and on the 60° day after germination. Experiment was conducted in a randomized block design with four N rates (0, 30, 60, 90 kg há-1), and with four replications. To evaluate the effect of nitrogen in the plant was conducted study Nitrogen use efficiency indices, agronomic efficiency, physiological and nutritional. For the second chapter scheme was installed in split plot in a randomized block design with four replications, with N rates (0, 30, 60 and 90 N.ha-1 kg) the plot and the evaluation period (T1 first sentence of 16º to 30º; T2 second sentence of 31º to 45º and T3 third sentence of 46º to 60º days after germination) to sub plot; where we evaluated the morphogenetic and structural characteristics of mombaça grass. It concluded that the recovery of applied N and agronomic efficiency at Mombasa grass increased with increasing doses. It observed, for all indices influence of the applied dose. A level of 90 kg N.ha-1, based on the indices studied, it is the most suitable for the establishment period of Mombaça grass. The increase in nitrogen rates positively influenced the appearance fees, leaf elongation, tiller density and number of live leaves per tiller. During the establishment period was identified different characteristics of the plant over the period, with higher leaf senescence rate (TSF), stem elongation rate (SER) and leaf elongation rate (LER) in T3 when compared with T2 and T1, T1 is already on the higher leaf appearance rate (LAR).